Pemikiran Taqi Misbah Yazdi tentang Etika Islam Kontemporer - Nurasiah Nurasiah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
This article attempts to explain the concept of Islamic ethics promulgated by Taqi Misbah Yazdi. Yazdi had placed himself as a proponent to the concept of rational ethics. To him, the propositions of ethics, along with moral expressions, have obviously explained a causality relation between an action and desired goals of ethics. In their prescriptive and descriptive forms, command and prohibitions manifest the relation between actions and the objectives of ethics along with the legal consequences behind them. As a result, this matter deals with meaning, objective, the value of objectivity, and rationality. Its objectives determine the extent of value and truth of certain action. Interestingly, this theory does not influence Yazdi to be trapped within utilitarianism materialist-positivist ethics nor it traps him into the dilemma of value relativity which occurs in the West’s theory of ethics. It can be obviously seen the originality and novelty of Yazdi’s thought; not in terms of his theory’s content, instead of his ability to use Western philosophy's ideas to clarify his opinions and concepts by combining Herbert Spencer’s evolutionism and Jeremy Bentham’s utilitarianism. Building his concepts on Mulla Sadra’s transcendental philosophy, Yazdi’s moral causality has successfully preserved the transcendental logic and its esoteric dimensions; an achievement that could not even be attained by Muslim groups who reject the law of causality.